Subduing Cultural Stereotype & Ethnocentrism In Business Organizations: A Soft Skills Stance - Mitashree Tripathy (Institut Teknologi Sepuluh Nopember, 2019)
Business organizations are highly dependent on culture and communication that define the essence of their existence. Researches indicate that while some organizations have successfully placed themselves in the global market places, there are still others who have deteriorated because of weak communication or insufficient assimilation with other organizations of different cultures. Recent studies argued that the accomplishment of the global business depends on successful cross cultural communication. This paper studies the role of cross cultural communication and the barriers that obstruct cross cultural effectiveness in business. The paper especially focuses on the cultural stereotype and ethnocentrism as the most powerful barriers in cross cultural communication and proposes solutions towards the relevance of soft skills in overcoming the barriers and ensuring success in business in unprecedented ways and their development in cross cultural management.